Efeito antitrombótico e hepatoprotetor do óleo essencial de Levisticum officinale - DENISE CAROLINE LUIZ SOARES (2025)
Cardiovascular and liver diseases represent a major challenge for public health, making the search for new therapeutic agents crucial. Furthermore, the identification of new treatments for these conditions must be accompanied by toxicity tests to ensure safety and efficacy. The aim of this study was to evaluate the antithrombotic and hepatoprotective action of Levisticum officinale essential oil (EOLO) in in vitro and in vivo experimental models. EOLO obtained from leaves from Hungary to capture the vapor was subjected to chemical characterization by gas chromatography coupled to mass spectrometry (GC-MS). The study protocol was approved by the UFMS Ethics Committee (CAAE 57842022.2.0000.0021, approval no. 5.445.802). To evaluate the in vitro and in vivo toxicity activity, the trypan blue exclusion test was performed on platelets (in vitro) and systemic toxicity was developed by an in vivo model of Galleria mellonella larvae. The evaluation of theantithrombotic activity was determined by the platelet aggregation assay performed by turbidimetry, using adenosine (ADP) and epinephrine receptor agonists (EPI). Coagulation was determined by active prothrombin time (PT) and partially activated thromboplastin time (aPTT). Platelet activation was assessed by P-selectin expression and reactive oxygen species (ROS) content by flow cytometry and fluorescence, respectively. To evaluate hepatoprotective activity, experiments were performed with male Balb/c mice (6 weeks, 25 ± 2 g). Four animals were reserved to obtain neutrophils used in the chemotaxis assay. The study protocol was approved by the UFMS Animal Ethics Committee (CEUA/UFMS 1.243/2022). The remaining animals were allocated into six experimental groups (n= 8/group).Group I (NC) and group II (APAP) received saline, paracetamol dissolution vehicle (APAP) and EOLO. Group III was pretreated with silymarin (SLM-200 mg/kg). Groups IV-VI received EOLO at different doses (50, 200 and 400 mg/kg). After 7 days, groups II-VI received APAP (300 mg/kg). Twelve hours after APAP administration, the animals were euthanized and blood was collected for biochemical analysis of liver function (AST, ALT and γ-GT). The livers of the mice were extracted for histological evaluations as well as biomarkers of inflammation and hepatic oxidative stress (nitric oxide - ●NO, myeloperoxidase -MPO, thiobarbituric acid reactive substances–TBARS e reduced glutathione-GSH). Neutrophil chemotaxis assay was performed using a microchemotaxis plate at concentrations of 1 - 60 mg/mL of EOLO. Chemical characterization of EOLO showed the presence of monoterpenes, including α-terpinyl acetate, β-phellandrene, β-myrcene, α-terpineol and (Z)-β-ocimene. EOLO demonstrated no toxicity in vitro and in vivo. EOLO resulted in platelet aggregation caused by ADP and EPI. Treatment of platelets with EOLO demonstrated a decrease in P-selectin expression as well as in ROS production. On the other hand, EOLO did not interfere with PT and aPTT. Regarding the evaluation of hepatoprotective activity, pretreatment with EOLO (50, 200 and 400 mg/kg) reversed the hepatic enzymatic alterations induced by APAP. In addition, MPO activity and hepatic ●NO production were increased. Histological sections show normal livers (without morphological alterations) in group I. Group II exhibited severe necrosis. Groups III-VI presented diffuse vacuolization, with less necrosis in the EOLO groups. EOLO included TBARS values and restored GSH concentrations. EOLO prevented neutrophil migration toward fMLP (10-6M). Neutrophil chemotaxis assay was performed using a microchemotaxis plate at concentrations of 1, 3, 10, 30 and 60 mg/mL of EOLO. The results demonstrated that EOLO has antiplatelet and hepatoprotective action. Furthermore, the findings suggest that such pharmacological effects possibly result from the antioxidant action of EOLO, since it was able to reduce the production of ROS in human platelets as well as protect against tissue oxidative stress induced by APAP, inhibiting the hepatic inflammatory process.